Hubungan Antara Dukungan Sosial Dengan Penyesuaian Diri Remaja Di Panti Asuhan - Fani Kumalasari; Latifah Nur Ahyani (Universitas Muria Kudus, 2012)
The purpose of this study is to investigate empirically the relationshipbetween social support with adjustment in adolescents in an orphanage. The subjects of this study are adolescents between the ages of 13 to 18 years in the Orphanage Darul Hadlonah Kudus. Method sampling using Quota Non Random Sampling.Measuring tool used is the scale of social support have been prepared on aspects raised by Sarafino in Oktavia, L (2002, p.17-18) which includesemotional support, support award, instrumental support, and support information. While the adjustment scale of self-prepared on aspects raised by Pramadi (1996, h.240) which covers aspects of Self Knowledge and Self Insight, aspect Objectifity Self Acceptance and Self, the aspect of Self Development and Self Control, Satisfaction aspect.Based on the analysis of research data with Product Moment by SPSS15.0 for Windows obtained from both the correlation coefficient rxy amounted to 0.339 with p of 0.011 (p smaller than 0.05) this means the hypothesis is accepted and showed relationship between social support with adolescent adjustment in an orphanage.